Social communication in intercultural space: response to actual challenges - Chernukha, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The study deals social communications in intercultural space. The information isprovided about liberal education in the modern society, dominants of its successful functioning is highlighted in accordance with modern requirements. Attention is accented on the priorities of development of the modern social adverse communication.